Can preoperative serum lactate dehydrogenase levels predict postoperative pulmonary complication following an emergency abdominal surgery? An observational study - Murugavel, Ananthakumar; Kanth, Vishnu; Palanivelu, Elamurugan Thirthar (International Surgery Journal, 2019)
Background: Postoperative pulmonary complications (PPC) are one of the commonest complications following gastrointestinal surgery. They lead to increase in morbidity and mortality. Lactate dehydrogenase (LDH) is an enzyme present in essentially all major organ systems. Studies have shown measurement of its activity levels and its isoenzyme pattern may provide additional information about lung and pulmonary endothelial cell injury. The objectives of the present study were to study the levels of serum LDH in patients with and without post-operative pulmonary complications following emergency abdominal surgery. Methods: The study was designed as an observational study. All patients ≥18 years of age undergoing gastrointestinal surgery, excluding those with prior lung pathology were included in the study. The demographic parameters, clinical parameters and laboratory parameters along with details of pulmonary complications were recorded. Serum LDH level were assessed on admission. Levels of serum LDH were compared between patients with and without post-operative pulmonary infections and were assessed for significance. Results: Incidence of PPC was 28% in our study. There was significant difference in the mean age in the group with and without PPC (p=<0.001). Smoking habit, serum albumin total protein and upper abdomen incision surgery were associated with increased incidence of PPC. Pleural effusion was the commonest PPC seen in patients. Serum LDH was not significantly associated with the incidence of PPC. Conclusions: Pre-operative serum LDH level is not a predictive factor for occurrence of postoperative pulmonary complication. Age, smoking, total protein, serum albumin, upper abdomen incision were found to associated with increased risk of PPCs.